PELATIHAN PEMBENTUKAN QANUN GAMPONG DALAM UPAYA MENUJU GOOD GOVERNANCE - Fuadi; Meta Suriyani; Siti Sahara (Global Science Society, 2020)
The administration of village governance in the districts of East Aceh, Keuchik and TuhaPeut has the authority to form a village qanun. However, in BuketSeulemak village, BiremBayeun sub-district, East Aceh Regency, there is no village qanun that can be a legal umbrella for adat issues in the community. The method used by the PKM team is to go directly to the location to provide training. The causal factor of no village qanun that can become a legal umbrella for customary issues in the BuketSeulemakgampong community is the BuketSeulemak village apparatus has not been able to independently in the formation of a village qanun that regulates and resolves adat issues in the community. After the training, the Keuchik, TuhaPeut, and the community understood their authority, frameworks and techniques, principles and content in the preparation of the qampunqanun and Keuchik regulations. Has also been able to independently in the formation of village qanun and Keuchik regulations.